Behaviour of steel structures in seismic areas : selected, peer reviewed papers from the 9th International Conference on the Behavior of Steel Structures in Seismic Areas (STESSA 2018), February 14-17, 2018, Christchurch, New Zealand - Mazzolani, Federico M.; MacRae, Gregory A.; Clifton, George Charles, 1955- (Trans Tech Publications, 2018)
This collection of papers and keynote lectures presented at the 9th International Conference on the Behaviour of Steel Structures in Seismic Areas (Stessa2018, Christchurch, New Zealand, February 14-17, 2018) is a comprehensive overview of the recent state-of-the-art developments in the field of seismic resistant steel structures. The book is a valuable source for all stakeholders involving scientists, professionals, companies, and authorities dealing with the reduction of the seismic risk in earthquake prone countries.
Keywords: Building, Iron and steel -- Congresses.; Steel, Structural -- Congresses.; Earthquake engineering -- Congresses.; Buildings -- Earthquake effects -- Congresses.; Earthquake resistant design -- Congresses.; Structural analysis (Engineering) -- Congresses.; elektronické knihy; electronic books